2021
DOI: 10.3390/nu13061837
|View full text |Cite
|
Sign up to set email alerts
|

Foxtail Millet Improves Blood Glucose Metabolism in Diabetic Rats through PI3K/AKT and NF-κB Signaling Pathways Mediated by Gut Microbiota

Abstract: Foxtail millet (FM) is receiving ongoing increased attention due to its beneficial health effects, including the hypoglycemic effect. However, the underlying mechanisms of the hypoglycemic effect have been underexplored. In the present study, the hypoglycemic effect of FM supplementation was confirmed again in high-fat diet and streptozotocin-induced diabetic rats with significantly decreased fasting glucose (FG), glycated serum protein, and areas under the glucose tolerance test (p < 0.05). We employed 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…In the present study, dietary addition of 0.1% nano-curcumin significantly upregulated the relative expression of GLUT2 in the liver of fish, indicating that glucose transporters transported glucose to hepatocytes for glycolysis. As the only metabolic pathway leading to glucose catabolism in all organisms, including fish, the important rate-limiting enzymes of glycolysis included GK, PFK, and PK (Seiliez et al, 2013;Ren et al, 2021). Our study found that the relative gene expressions of GK, PFK, and PK were significantly increased in the 0.2% nano-curcumin group compared with the control group, demonstrating that nanocurcumin could reduce serum glucose levels by promoting the expression of key rate-limiting enzyme genes in glycolysis.…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, dietary addition of 0.1% nano-curcumin significantly upregulated the relative expression of GLUT2 in the liver of fish, indicating that glucose transporters transported glucose to hepatocytes for glycolysis. As the only metabolic pathway leading to glucose catabolism in all organisms, including fish, the important rate-limiting enzymes of glycolysis included GK, PFK, and PK (Seiliez et al, 2013;Ren et al, 2021). Our study found that the relative gene expressions of GK, PFK, and PK were significantly increased in the 0.2% nano-curcumin group compared with the control group, demonstrating that nanocurcumin could reduce serum glucose levels by promoting the expression of key rate-limiting enzyme genes in glycolysis.…”
Section: Discussionmentioning
confidence: 60%
“…NF-kB and IL-6 act as the main regulators of inflammation, which modulate various aspects of innate and adaptive immune responses. The activation of NF-kB/IL-6 is associated with chronic inflammation, autoimmune diseases and cancer [138] . In particular, NF-kB emerges as one of the key factor linking metabolism, inflammation and insulin function, which regulates energy homeostasis and metabolic adaptation by modulating the balance between glycolysis and oxidative phosphorylation [139] , [140] .…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%
“…A 16s rRNA sequencing analysis showed that FM consumption significantly increased the relative abundances of Lactobacillus and Ruminococcus_2, which were significantly negatively correlated with FG and 2 h glucose. Subsequently, a Spearman's correlation analysis indicated a complicated set of interdependences among the gut microbiota and metabolic parameters [118].…”
Section: Effects On Diabetesmentioning
confidence: 99%